Analisa Karakteristik Pengujian Co-Firing Biomassa Bagasse Tebu di PLTU Rembang Kapasitas 2×315 MW - Riris Destalia; Enny Aryanny (Yayasan Literasi Sains Indonesia, 2024)
Energy utilization in power plants in Indonesia significantly relies on fossil energy sources, especially those obtained from power plants that use coal as the main fuel. The aim of testing co-firing of sugarcane bagasse biomass is to determine the effect of co-firing on the reliability and main parameters of coal-fired power plants and to obtain an overview of the feasibility of implementing co-firing which includes aspects of operational technical evaluation, production cost evaluation and environmental evaluation. The biomass effectiveness test was carried out at PLTU Rembang, with test variables of 100% coal, co-firing test of 1.25% and 2.5% sugarcane bagasse biomass with a maximum operational load of 315 MW for 6 hours. The results of data analysis were carried out descriptively. The tested sugarcane bagasse biomass had a calorific value of 2947 kCal/kg. Meanwhile, the coal used in PLTU Rembang has a calorific value of 4286 kcal/kg. The SO2 emission test results decreased in the Co-firing test of 1.25% sugarcane bagasse and increased in the Co-firing test of 2.5% sugarcane bagasse compared to the 100% coal test, while the NOx emission test results produced during the co-firing test firing 1.25% and 2.5% sugarcane bagasse biomass has a lower value than using 100% coal. The cost of co-firing electricity production from sugarcane bagasse biomass is 1.25% and 2.5% cheaper than the cost of producing 100% coal electricity. To reduce electricity production costs, the sugarcane bagasse biomass co-firing scheme needs to be emphasized by referring to HPT determination in accordance with PLN Perdir No.0004/DIR/2022, so that co-firing electricity production costs can be more economical.